Comparative study of different activation treatments for the preparation of activated carbon: a mini-review. (1st September 2017) - Din, Muhammad Imran; Ashraf, Sania; Intisar, Azeem
In this review, various methods of preparation of activated carbon from agricultural and commercial waste material are reviewed. In addition, we also discuss various activation treatments using a comparative approach. The data are organised in tabulated form for ease of comparative study. A review of numerous characterisation techniques is also provided. The effect of time and temperature, activation conditions, carbonisation conditions and impregnation ratios are explained and several physical and chemical activation treatments of raw materials and their impact on the micro- and mesoporous volumes and surface area are discussed. Lastly, a review of adsorption mechanisms of activated carbon (AC) is also provided.